Complete mitochondrial genome of Angelica dahurica and its implications on evolutionary analysis of complex mitochondrial genome architecture in Apiaceae - Li, Yuan-Yuan; Liu, You-Yan; Zeng, Xu; Wu, Ping; Li, Qing-Miao; Guo, Shun-Xing; Hao, Zhi-Gang (Frontiers in Plant Science, 2024)
Angelicae dahuricae is a kind of Chinese traditional herbs with economic and ornament value, widely distributed in China. Despite its significance, there have been limited comprehensive investigations on the genome of A. dahuricae, particularly regarding mitochondrial genomes. To investigate the conversion between mitochondrial genome and chloroplast genome, a complete and circular mitochondrial genome was assembled using Oxford Nanopore Technologies (ONT) long reads. The mitochondrial genome of A. dahuricae had a length of 228,315 base pairs (bp) with 45.06% GC content. The mitochondrial genome encodes 56 genes, including 34 protein-coding genes, 19 tRNA genes and 3 rRNA genes. Moreover, we discovered that 9 homologous large fragments between chloroplast genome and mitochondrial genome based on sequence similarity. This is the first report for A. dahuricae mitochondrial genome, which could provide an insight for communication between plastid genome, and also give a reference genome for medicinal plants within the Angelica family.